Experiment on aeroacoustic characteristics of a NACA0012 airfoil with rime ice model on the leading edge. (April 2021) - Xiao, Chunhua; Tong, Fan
Abstract: Ice accretion changes the shape of the airplane aerodynamic surface, resulting in not only the degradation of aerodynamic performance but also the variation of the aeroacoustic characteristics. In order to explore the effect of the ice accretion on the aerodynamic noise, a NACA0012 airfoil with rime ice model on the leading edge was investigated experimentally in an aeroacoustic wind tunnel using far-field microphone array measurements. Two rime ice models of different ice thickness were attached on the airfoil leading edge. The results were compared with the baseline airfoil at various airflow speeds and different angles of attack. The experiments reveal that the ice model increases the maximum far-field sound pressure level ( SPL ) by 9.5 dB in the frequency band of 7–25 kHz. And the averaged OASPL difference between airfoil with ice model and baseline airfoil is linear with the 1/2 power of ice thickness. Higher angle of attack results in larger increase of the noise level. Steady RANS simulation as well as large eddy simulation was also performed to uncover the mechanism of the noise increase by the rime ice model. The presence of the rime ice model altered the local flow field around the leading edge of airfoil, resulting in the variation of airfoil surface pressure fluctuation and far-field acoustic characteristics. It would enhance the noise radiation of the airfoil, which was verified by the sound power level ( PWL ) of airfoil with ice model. It may provide an idea to develop a novel ice detection method based on the far-field noise increment by the ice model.